The effects of pajama fabrics' water absorption properties on the stratum corneum under mildly cold conditions - Yao, Lei; Li, Yi; Gohel, Mayur Danny Indulal; Chung, Waiyee J. (Journal of the American Academy of Dermatology, 2011)
The interaction of textiles with the skin is a fertile area for research. The aim of this study was to investigate the effects of clothing fabric on the stratum corneum (SC) under mildly cold conditions. A longitudinal controlled parallel study was designed to investigate the effects of the liquid/moisture absorption properties of pajama fabrics on the SC water content, transepidermal water loss, skin surface acidity (pH), and sebum. The hygroscopicity of pajama fabrics had significant associations with the SC water content and transepidermal water loss on the skin of the volunteers' backs. Sebum in the hydrophilic cotton group was slightly lower than in the polyester groups and hydrophobic cotton groups. Subjects felt warmer in the hydrophobic groups than in the hydrophilic groups. The hydrophilicity of the fabric also showed an association with overnight urinary free catecholamines. In this study, detailed components of sebum were not analyzed. The hygroscopicity of the fabric may be a key factor influencing SC hydration during daily wear under mildly cold conditions.